Composites and Their Properties - Hu, Ning (IntechOpen, 2012)
Composites are a class of material, which receives much attention not only because it is on the cutting edge of active material research fields due to appearance of many new types of composites, e.g., nanocomposites and bio-medical composites, but also because there are a great deal of promises for their potential applications in various industries ranging from aerospace to construction due to their various outstanding properties. This book mainly deals with fabrication and property characterization of various composites by focusing on the following topics: functional and structural nanocomposites, numerical and theoretical modelling of various damages in long fiber reinforced composites and textile composites, design, processing and manufacturing technologies and their effects on mechanical properties of composites, characterization of mechanical and physical properties of various composites, and metal and ceramic matrix composites. This book has been divided into five sections to cover the above contents.